1996
DOI: 10.2134/jpa1996.0241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tillage and Rotation on Agronomic Performance of Corn and Soybean: Twenty-Year Study on Dark Silty Clay Loam Soil

Abstract: In the U.S. Corn Belt, tillage without plowing was used on more than 50% of corn (Zea mays L.) and soybean [Glycine max (L.) Merr.] acreage in 1994, while no‐till planting was used on about 30% of the acreage. Few research studies have evaluated these reduced tillage systems for 20 yr or more. This study includes plow, chisel, ridge, and no‐till systems in continuous corn, corn after soybean, soybean after corn, and continuous soybean rotations. The experiment was conducted on Chalmers (fine‐silty, mixed, mesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 17 publications
9
70
0
Order By: Relevance
“…Higher maize GY A in conventional tillage than in no-till was previously reported for Indiana by Barber (1971), Mengel et al (1982), West et al (1996), and Boomsma et al (2010), and for other Corn Belt states by Fink and Wesley (1974), Huggins and Pan (1993), Vetsch andRandall (2004), andBos (2012). Proportional differences between tillage systems and N rates were smaller in 2011 and 2012 relative to 2010, presumably as a result of plant growth/grain fill limitations from the hailstorm damage in 2011, and drought stress in 2012 (Eck, 1984;Bennett et al, 1989).…”
Section: Grain Yieldmentioning
confidence: 60%
See 1 more Smart Citation
“…Higher maize GY A in conventional tillage than in no-till was previously reported for Indiana by Barber (1971), Mengel et al (1982), West et al (1996), and Boomsma et al (2010), and for other Corn Belt states by Fink and Wesley (1974), Huggins and Pan (1993), Vetsch andRandall (2004), andBos (2012). Proportional differences between tillage systems and N rates were smaller in 2011 and 2012 relative to 2010, presumably as a result of plant growth/grain fill limitations from the hailstorm damage in 2011, and drought stress in 2012 (Eck, 1984;Bennett et al, 1989).…”
Section: Grain Yieldmentioning
confidence: 60%
“…Despite the large differences in GY A between the tillage systems and N rates, GY A at the lower N rate with parallel NH 3 placement did not differ from GY A attained with the higher N rate with diagonal NH 3 placement; neither did GY A with parallel application in the no-till tillage system differ significantly from GY A attained in conventional tillage with diagonal application. The lower N rate lowered GY A by 0.8 and 1.2 Mg ha -1 in conventional till and no-till systems, respectively, within the tillage system × N rate interaction; however GY A for the 145 kg N ha -1 in conventional tillage did not differ significantly from that of the no-till at 202 kg N ha -1 (data not shown).Higher maize GY A in conventional tillage than in no-till was previously reported for Indiana by Barber (1971), Mengel et al (1982, West et al (1996), andBoomsma et al (2010), and for other Corn Belt states by Fink and Wesley (1974), Huggins and Pan (1993), Vetsch andRandall (2004), andBos (2012). Proportional differences between tillage systems and N rates were smaller in 2011 and 2012 relative to 2010, presumably as a result of plant growth/grain fill limitations from the hailstorm damage in 2011, and drought stress in 2012 (Eck, 1984;Bennett et al, 1989).…”
mentioning
confidence: 59%
“…The results differ depending on the type of crop, soil and weather patterns (Borin and Sartori, 1995). West et al (1996) observed poor yielding of soybean under NT when compared with other tillage systems in a corn-soybean rotation during some drought years. In turn, Heenan et al (2000) showed that the mean annual seed yields of lupin ranged from 0.26 to 3.15 t ha -1 in years and differences in lupin seed yields between tillage (conventional cultivation and direct drilling) and stubble treatments over time were marginal.…”
Section: Discussionmentioning
confidence: 96%
“…Numerous experiments have shown that soybean yields are increased when this crop is grown in rotation with non-leguminous crops [62][63][64][65][66]. Changing from soybean to another crop breaks the lifecycle of soybean cyst nematodes (SCN's).…”
Section: Legumes and Crop Rotationsmentioning
confidence: 99%